2000
DOI: 10.1086/313642
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia, Neutrophil Dysfunction, and Bacterial Infection in Patients with Human Immunodeficiency Virus Disease: The Role of Granulocyte Colony-Stimulating Factor

Abstract: Neutropenia frequently complicates infection due to human immunodeficiency virus (HIV). The etiology of neutropenia in this setting includes bone marrow infection or infiltration, myelosuppressive therapies, the presence of antibodies to HIV, and accelerated apoptosis. Protection against microbial invaders by neutrophils is further compromised by impaired chemotaxis and phagocytosis, production of toxic oxygen species, and expression of cellular adhesion molecules. Neutropenia is a significant risk factor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 66 publications
3
59
0
5
Order By: Relevance
“…In addition, HIV-associated neutropenia and monocytopenia, as well as dysfunction of several of the protective activities of these cells, including chemotaxis to bacterial proteins, as well as antimicrobial activity, are potential contributors to predisposition to pneumococcal disease [40,41].…”
Section: Pneumococcal Pneumoniamentioning
confidence: 99%
“…In addition, HIV-associated neutropenia and monocytopenia, as well as dysfunction of several of the protective activities of these cells, including chemotaxis to bacterial proteins, as well as antimicrobial activity, are potential contributors to predisposition to pneumococcal disease [40,41].…”
Section: Pneumococcal Pneumoniamentioning
confidence: 99%
“…In fact, it can be suggested that enhancing levels of LT biosynthesis may indirectly contribute to the immunostimulation resulting from administering cytokines such as CSFs (Ref. 96 and see above). Alternatively, tissue levels of LTs at a site of infection might be amplified by their direct administration.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Elevated neutrophil counts were previously reported in a 33-year-old woman with AIDS who had disseminated aspergillosis affecting the brain and spine (Martinez et al, 2009). Furthermore, HIV-infected patients have defects in neutrophil function as well as activation of neutrophils, contributing to this dysfunction, which may manifest at all stages of HIV disease (Kuritzkes, 2000).…”
Section: Discussionmentioning
confidence: 86%